Dirigo Health: A Small Business Perspective - Cook, Deborah (Maine Policy Review, 2003)
In her commentary Deborah Cook, executive director of the Maine Small Business Alliance, discusses Dirigo Health from the viewpoint of small businesses, whose employees and families, along with the self-employed, represent the largest proportion of uninsured in Maine’s population. She notes that rising costs of health care and insurance are a major threat to the viability of small businesses.